Perceived Determinants of Daily Food Choices among University Students - Arya Desta Bimantara; Sita Nurmasitah (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
Food choice behavior among university students is an important public health issue because eating patterns developed during young adulthood may persist into later life. This study aimed to examine students’ perceived determinants of daily food choices using the Food Choice Questionnaire (FCQ). A quantitative descriptive design with a cross-sectional survey approach was applied to 150 undergraduate students from the Culinary Education Program at Universitas Negeri Semarang, Indonesia, selected through random sampling based on the Slovin formula. Data were collected using the FCQ consisting of 36 items across nine dimensions and analyzed using descriptive percentage analysis. The results showed that price was the most influential determinant of daily food choices (86.28%), followed by mood (83.78%), convenience (83.63%), sensory appeal (83.58%), and health (83.14%). Natural content (79.56%) and weight control (72.39%) were perceived as moderately influential, while ethical concern was the least influential determinant (68.83%). These findings indicate that students’ food choices are shaped primarily by economic, emotional, and practical considerations, suggesting an intention–behavior gap in which health awareness does not consistently translate into daily food choice behavior.